Perception and Expectation of Viewers and Proposed Business Models for Local TV Stations: Case of Internet Local TV Stations in West Java Province-Indonesia - Umi Kaltum; Wa Ode Zusnita Muizu; Merita Bernik (Jurnal Bisnis Manajemen, 2018)
Local content is an important resource for Indonesia because it has economic as well as cultural values. Local content has the value of local wisdom, believed to be able to build a strong national identity and is able to survive amid the uncertainty era. Presently, the Indonesian local content barely exists, being hit by the global content in various media. Local television, closely related to the content area, is expected to encourage the growth of local content from all regions of the country. This research is aimed at determining the role of internet local TV in West Java in developing the local content which has global competitiveness. This can then be utilized by all local TV stations in Indonesia to expand the broadcast nationally and globally by using the Internet television technology.The method used is a descriptive survey using quantitative and qualitative research approach. The sample consists of 422 viewers and 12 local TV stations in West Java. The results obtained are the perception and expectations of the local TV viewers in West Java from the aspect of Quality Service with the dimensions of tangibility, Assurance, Empathy, Reliability, and Responsiveness, as well as the Business Model Canvas (BMC) of local TV stations in West Java.